(untitled) (SciELO Preprints, 2021)
Purpose: To determine the influence of emotional alterations in the arterial stiffness index and cardiovascular risk of pre-hypertensive patients. Methods: A cross-sectional study was carried out in 48 pre-hypertensive patients. Emotional alterations, global cardiovascular risk and arterial stiffness index were evaluated. The PPG technique was used to record the arterial pulse wave in the first finger of the lower right limb, using the ANGIODIN® digital plethysmograph. Results: Pre-hypertensive patients with emotional alterations had major Weight, Body Mass Index, systolic blood pressure, diastolic blood pressure and arterial stiffness index with respect to patients who did not find emotional alterations. In pre-hypertensive patients, 58.3% presented a positive Cornell test, 39.6% of them female, and 18.8% male. There was a significant relationship (p<0.001) between the presence of emotional disturbances and moderate cardiovascular risk. Conclusions: Emotional alterations in pre-hypertensive patients is associated with an increase in arterial stiffness and an increased global cardiovascular risk.